Microbiologically influenced corrosion of mild steel and stainless steel by pseudomonas aeruginosa in enriched artificial sea water / Ahmad Hisham Mohamed Aris - Mohamed Aris, Ahmad Hisham (2015)
Corrosion damage in the form of pitting corrosion was observed on both mild steel ASTM 283-D and stainless steel 304 after being exposed to Pseudomonas aeruginosa-inoculated enriched artificial seawater (EASW) after 7 days and 14 days exposure period. To determine the difference in corrosion severity between these two steels, characterization of the samples were carried out with the following instruments; AUTOLAB Potentiostat, Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive Spectrum (EDS), Infinite Focus Microscope (IFM) and Surface Roughness Profiler. Corrosion phenomenon was confirmed by the increase of corrosion rate and surface roughness values. Imaging of the pitting corrosion with FESEM and IFM together with elemental composition of the pitting with EDS confirmed the form of corrosion that took place on both steels in the presence of the bacterium. The link between biofilm and pitting corrosion was established with biofilm imaging by IFM. Determination of pitting shape by using its volume and projected area were considered to be more accurate than with pitting depth and width. In the case of control samples in sterile EASW, uniform corrosion was noticeable on mild steel but was not observed on stainless steel, which reinforced the fact that its passive chromium oxide film played a crucial role in corrosion prevention. The study revealed that pitting corrosion on mild steel was found to be more severe than those on stainless steel since its propagation in the vertical direction can cause earlier perforation of the base steel.